Offline accessible system for agricultural e-commerce using unstructured supplementary services data application (2018)
E-commerce has a major impact in the agricultural sector. The way people go about purchasing agricultural products and the way the farmers sell them are important. Sometimes, buyers have to travel far distances to get agricultural products and getting the right quality is not guaranteed. Various market prices cannot be compared because buyers do not have all the time and resources to visit every agricultural farm. Hence, the need for an offline accessible means of trading electronically which would help farmers and other buyers, make their appropriate business transactions online. This study is concerned with the application of Unstructured Supplementary Services Data Application (USSD) and Short Messaging Service to connect farmers to an e-commerce platform. Entity relationship model use case diagram and Unified Modeling Language class diagram were used in the system design. The farmer accesses the offline service via a USSD short code (offline module) and they can then manage their crop inventory and other basic details. Their crop inventory is then synced to the online e-commerce platform for buyers to compare prices, view crop availability and order crops. The farmer can either accept or reject to do business with a buyer via SMS and the buyer will be notified in the All Orders section of the platform. The system helps to connect farmers that do not have smartphones and Internet access to an online marketplace thereby increasing their access to market.